Living with tinnitus and hyperacusis - Laurence McKenna; David Baguley; Don J McFerran (Sheldon, 2010)
Tinnitus can be a terrible affliction, both for the individual, and also for friends and family. Hyperacusis, acute sensitivity to noise, can also seriously interfere with everyday life. These conditions are common in adults and may affect children, too. The good news is that prospects for recovery have never been better, thanks to advances in scientific understanding and therapy. There are techniques that can be Read more...